Habitus And Capital In Rejung Art In Semende Ethnic Communities In Tanjung Bulan Village, OKU Selatan District, South Sumatra Province - Fadhilah Hidayatullah; Widodo Widodo; Ayu Niza Machfauszia; Slamet Haryono (Universitas Negeri Semarang, 2023)
This research is motivated by a Rejung art that originates from lamentations. At first, only random utterances were used to communicate sorrowful moods, but now, as a patterned and systematic work of art, they become rhymes. Pantun which is characterized by the regional language of the Semende ethnic group which conveys messages according to the circumstances culprit. However, the sadness that is patterned through the poetry/lyrics of rhymes and kenjun or melodic swings cannot be separated from Rejung's artwork itself. This study aims to determine the habitus and capital of rejung art in the Semende community in South Sumatra province. The method used is descriptive qualitative. The results and findings of the research show that; Rejung art as a medium for communicating grief through rhymes, which have meanings and messages according to the wishes and needs of the performer. Lamentation is the behavior of someone who is experiencing sadness. Forms of behavior in the form of speech and crying. Speech in the form of oral speech is carried out with the rhythmic accompaniment of crying. Serving rhythm with a distinctive melody reflects a deep sadness. Treatment automatically invites and encourages the environment to be and feel the same way. Although without listening to the words of the perpetrator , the surrounding environment feels a deep sense of sadness . Through mumbling and crying rhythms that reflect a sadness , the environment has been formed and framed in an atmosphere of deep sadness. Habits of the community as perpetrators of grief can change and invite an atmosphere of sadness to the surrounding community, become a patterned habit. There is a type of rejung which is known as fate which has a distinctive style and melody in lamenting the fate that is being experienced by the perpetrator. Sadness is illustrated through the strains of melodies and poetry or rhyme lyrics that elevate one's own sad condition . So that modality can seen from aspect environment education , because art palm trees as material learning , so still can endure through eye learning _ very relevant lecture . Habits seen from third aspect of being habits that occur in society Semende in the province of South Sumatra, namely : ( a ) . Lamenting full of sorrow ; (b). Crying with tears ; and (c) Rhyming lamentations and weeping in sorrow . Between habitus and modality each other complement and support For survival art palm trees So that its existence can still awake in the middle society , let alone one College has _ apply it through teaching material on the eye lecture and graded can become very positive force .